FLACC 16.1 : Werkplaats voor beeldende kunstenaars. - Krueger, Anders; Nouwen, Luuk; Sealy, Mark; de Almeida, Bruno (Genk : FLACC, 2016)
Gaisumov, Aslan ; Paglen, Trevor ; Koeman, Jean Bernard ; De Paula, Daniel ; Araújo, Vasco
boek